Social Masks and Identity Construction in Lualhati Bautista’s Bata... Pa'no Ka Ginawa? - Marie Rose L. Costes (Randwick International of Education and Linguistics Science Journal, 2024)
This research employs a descriptive qualitative method, combining textual analysis with cultural and socio-cultural perspectives, to investigate the portrayal of social masks, identity construction, and resilience in Lualhati Bautista's novels, focusing on "Bata, Bata... Pa'no Ka Ginawa?" The study explores how selected characters navigate social roles, adopt personas, and engage in impression management within Filipino society. Through close reading and theoretical interpretation using Goffman's and Mead's frameworks, the research uncovers insights into the intricate dynamics of identity construction, social interaction, and resilience depicted in Bautista's narratives. Significant findings include resilience among characters and its intersection with identity construction and social interaction. Additionally, the study reveals the influence of cultural norms, historical events, and socio-economic factors on characters' identity construction and resilience strategies. It also highlights moments of authenticity, vulnerability, and resistance, analyzing how they challenge or reinforce social masks and identity performances. Overall, the research contributes to understanding the complexities of Filipino identity and resilience in contemporary society as portrayed in literature.